Online Safety for Children and Youth under the 4Cs Framework-A Focus on Digital Policies in Australia, Canada, and the UK - Yujin Jang; Bomin Ko (MDPI AG, 2023)
This study analyzes the previous literature on the online safety of children and youth under "the 4Cs risk framework" concerning contact, content, conduct, and contract risks. It then conducts a comparative study of Australia, Canada, and the UK, comparing their institutions, governance, and government-led programs. Relevant research in Childhood Education Studies is insufficient both in quantity and quality. To minimize the four major online risks for children and youth in cyberspace, it is necessary to maintain a regulatory approach to the online exposure of children under the age of 13. Moreover, the global society should respond together to these online risks with "multi-level" policymaking under a "multi-stakeholder approach". At the international level, multilateral discussion within the OECD and under UN subsidiaries should continue to lead international cooperation. At the domestic level, a special agency in charge of online safety for children and youth should be established in each country, encompassing all relevant stakeholders, including educators and digital firms. At the school and family levels, both parents and teachers need to work together in facilitating digital literacy education, providing proper guidelines for the online activities of children and youth, and helping them to become more satisfied and productive users in the digital era.